Film properties of plastics and elastomers - McKeen, Laurence W. (Elsevier, 2012)
Now in its 3e, Film Properties of Plastics and Elastomers, has been extensively revised. This is the only data handbook available on the engineering properties of commercial polymeric films. It details many physical, mechanical, optical, electrical, and permeation properties within the context of specific test parameters, providing a ready reference for comparing materials in the same family as well as materials in different families. Data is presented on the characteristics of 47 major plastic and elastomer packaging materials. New to this edition, the resin chapters each contain te.
At head of title: Plastics Design Library.
Keywords: Plastics.; Elastomers.; elektronické knihy; electronic books